Titanium/FRP hybrid sandwich: in-plane flexural behaviour of short beam specimens - C. Bellini; V. Di Cocco; F. Iacoviello; L.P. Mocanu; L. Sorrentino; R. Borrelli; S. Franchitti (Fracture and Structural Integrity)
Adopting novel sandwich structures with FRP (Fibre Reinforced Polymer) skins and a metallic lattice core, both of which have high specific strength and stiffness, is one way to achieve better mechanical performance while remaining lightweight. Flexural stress is a load pattern that frequently occurs in the structural frame components of automobiles; nonetheless, while the in-plane load scheme has scarcely been examined, the out-of-plane load one has. As a result, the former configuration received consideration in this work. Moreover, short beam specimens were taken into account. The mechanical response of specimens with three different kinds of composite materials as skin material was analysed. The skins were made of CFRP (Carbon Fiber Reinforced Polymer), with two different weaving styles, and AFRP (Aramid Fiber Reinforced Polymer). All-titanium specimens were studied, too. Similar maximum loads and maximum displacement at break were recorded for both CFRP and AFRP specimens, while the all-titanium one resulted stronger. In terms of the load-displacement curves, the first section featured an initial linear phase, followed by a minor load drop, likely attributed to the breakage of fibres. The CFRP specimens showed a sharp fracture of the skin fibres, while for the AFRP, a fraying was observed.